Florid cemento-osseous dysplasia: A case report - Arush Thakur; Shuddhodhan Gaikwad; Jagdish Vishnu Tupkari; Easwaran Ramaswami (Wolters Kluwer Medknow Publications, 2021)
Cemento-osseous dysplasia is non-neoplastic, reactive fibro-osseous lesions that affect the tooth-bearing areas of the jaws. Osseous dysplasia is further divided into three subtypes: Periapical osseous dysplasia, focal osseous dysplasia, and florid osseous dysplasia. We hereby, present a case of florid cemento-osseous dysplasia occurring in a 40-year old dentulous Indian woman. The patient presented with lesions involving the mandibular right and left quadrant.